Swelling and re-swelling performance of glutaraldehyde crosslinked wet chitosan hydrogels - Kaçoğlu, H Songül; Ceylan, Özgür; Çelebi, Mithat (İdris Karagöz, 2025)
Chitosan (Chi) is frequently used in hydrogels because of its natural characteristics. It is environmentally friendly, biodegradable, and does not include any harmful substances. Chitosan hydrogels were chemically synthesized by cross-linking with glutaraldehyde (GA) at various ratios ranging from 1% to 10% (w/w), employing two types of molecular weight chitosan. The degree of swelling of wet hydrogels (non-drying) was examined at pH 2.0, 5.6, and 7.4. After the swollen hydrogels dried, their re-swelling capabilities were examined in distilled water. Chemically cross-linked chitosan hydrogels were found to be stable, so the hydrogels were able to swell repeatedly 5 times without losing any of their swelling properties. The storage modulus properties of chitosan hydrogels were measured using a Discovery Hybrid Rheometer-1 at different temperatures. The storage moduli of chitosan hydrogels remained stable as temperature increased, with maximum values of 0.01 MPa and 0.02 MPa for low and medium molecular weight hydrogels. The viscosity of chitosan solutions was determined using two instruments: a Discovery Hybrid Rheometer-1 at 25 °C at different shear rates, and a Brookfield Viscometer. The viscosity of low and medium molecular weight chitosan solutions were measured using a Brookfield Viscometer, resulting in values of 101.5 and 333.5 cps, respectively.

Chitosan (Chi) is frequently used in hydrogels because of its natural characteristics. It is environmentally friendly, biodegradable, and does not include any harmful substances. Chitosan hydrogels were chemically synthesized by cross-linking with glutaraldehyde (GA) at various ratios ranging from 1% to 10% (w/w), employing two types of molecular weight chitosan. The degree of swelling of wet hydrogels (non-drying) was examined at pH 2.0, 5.6, and 7.4. After the swollen hydrogels dried, their re-swelling capabilities were examined in distilled water. Chemically cross-linked chitosan hydrogels were found to be stable, so the hydrogels were able to swell repeatedly 5 times without losing any of their swelling properties. The storage modulus properties of chitosan hydrogels were measured using a Discovery Hybrid Rheometer-1 at different temperatures. The storage moduli of chitosan hydrogels remained stable as temperature increased, with maximum values of 0.01 MPa and 0.02 MPa for low and medium molecular weight hydrogels. The viscosity of chitosan solutions was determined using two instruments: a Discovery Hybrid Rheometer-1 at 25 °C at different shear rates, and a Brookfield Viscometer. The viscosity of low and medium molecular weight chitosan solutions were measured using a Brookfield Viscometer, resulting in values of 101.5 and 333.5 cps, respectively.
Swelling and re-swelling performance of glutaraldehyde crosslinked wet chitosan hydrogels
Thesis Project (2020/YL/0025).
Keywords: Functional Materials; Fonksiyonel Malzemeler